A patient-centred care model for patients with complicated multimorbidity: Protocol for a pilot cluster randomised trial in general practice, municipalities, and hospitals. - Sanne Lykke Lundstrøm; Nina Kamstrup-Larsen; Barbara Ann Barrett; Louise Marie Bidstrup Jørgensen; Solvej Skriver Hansen; John Sahl Andersen; Bolette Friderichsen; Anders Stockmarr; Anne Frølich (PLoS ONE)
Introduction Current care is inadequate for patients with complicated multimorbidity, and frequently results in fragmented care. There is no widely agreed-upon optimal organisation of healthcare services for this patient group. By drawing upon existing literature and prior studies, we developed a patient-centred complex intervention for multimorbidity (CIM) and subsequently refined it into CIM version 2 (CIM2). This paper describes the study protocol for a pilot cluster randomised control trail (RCT) evaluating the effectiveness of a general practice-based intervention. Methods CIM2 aims to support integrated care for patients with complicated multimorbidity. CIM2 comprises five elements: 1) Training healthcare professionals, 2) an extended overview consultation in general practice, 3) a nurse care coordinator in general practice supporting the planning of the patient trajectory, 4) follow-up care services in general practice, and 5) improving the integration of care between general practice, municipality, and hospital. The pilot cluster RCT involve 350 patients with complicated multimorbidity across 14 general practices in Region Zealand and The Capital Region of Denmark. Patients are randomly assigned to either the intervention group or the usual care group. The primary outcome measure is the patients experience of quality of care measured by the Patient Assessment Chronic Illness Care Questionnaire (PACIC). Secondary outcomes include the patient's health-related quality of life, measured by the EuroQol-5 Domain questionnaire (EQ-5D-5L) and the treatment burden measured by the Multimorbidity Treatment Burden Questionnaire (MTBQ). Data on chronic conditions, healthcare utilization, and demographic information such as sex, age, and educational attainment will be collected from national registries. The outcome measures will be recorded before, during, and after implementing the intervention. Qualitative evaluation will include semi-structured interviews with healthcare professionals across various sectors as well as patients. The cost-effectiveness and Incremental Cost Effectiveness Ratio (ICER) of the CIM2 will be assessed using Diagnose Related Group rates. Trial registration ClinicalTrials.gov Identifier: NCT05406193. https://clinicaltrials.gov/study/NCT05406193.